Pengaruh Variasi Diameter Groundstrap Terhadap Daya Dan Torsi Pada Sepeda Motor Honda New Mega Pro 150 Cc Tahun 2013 - M. Ilham Fredian Syah , M. Ilham; Budiyono, Budiyono; Prasetyo, Imam (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
ABSTRACT When electricity flows through the spark plug wire, an electromagnetic field occurs which will cause damage to the sparks at the tip of the spark plug electrode in the form of a decrease in the peak of combustion. One way to overcome this problem is to stabilize the electric current generated by the coil by using an ignition booster. There are various types of Ignition Booster, one of which is Groundstrap. Groundstrap is one type of Ignition Booster whose function is to stabilize the electric current generated by the coil so that the spark plug can be bigger and more stable. The purpose of this research is to find out which of the three research variables adding the Groundstrap has the best effect on power and torque on a new Honda motorcycle. mega pro 150 cc in 2013. In this study, power and torque were tested with the addition of three variables of Groundstrap wire diameter, namely 0.4 mm, 0.6 mm, and 0.8 mm, with the same number of turns, namely 50 turns. then tested using the Dynotest tool. From the results of tests that have been carried out on three Groundstrap variables, that there is an effect of adding Groundstrap to power and torque, then the best research results are when using the Groundstrap variable diameter of 0.8 mm with the results of the research that at 8500 RPM engine speed produces a power of 0.8 mm. 13.7 HP, and at 6000 RPM engine speed produces a torque of 13.73 Nm. Keywords: Groundstrap, Power and Torque, Dynotest